Co-Combustion of Pellets from Soma Lignite and Waste Dusts of Furniture Works - Deveci, N. Duranay; Yilgin, M.; Pehlivan, D. (Taylor & Francis Inc, 2008)
In this work, volatiles and char combustion behaviors of the fuel pellets prepared from a low quality lignite and the dusts of furniture works and their various blends were investigated in an experimental fixed bed combustion system through which air flowed by natural convection. Combustion data obtained for varied bed temperatures, mass of pellets, and blend compositions has showed that ignition times of the pellets decreased and volatiles combustion rates tended to increase with the burning temperature. It was concluded that some synergy had existed between lignite and lower ratios of furniture work dusts, which was indicated by a prompt effect on the volatiles combustion rates. Char combustion rates of blend pellets have depended predominantly on the amount of lignite in the blend. The amounts of combustion residues of the pellets were considerably higher than those calculated from individual ash contents of the raw materials and related to lignite ratio in the blends.
Keywords: Co-combustion; Lignite; Waste; Dusts of furniture works; Pellet